Synopsis: Social networks and factor markets: Panel data evidence from Ethiopia - Abay, Kibrom A.; Kahsay, Goytom A; Berhane, Guush (International Food Policy Research Institute, 2015)
In the absence of well-established factor markets, the roles of indigenous institutions and social networks as mobilizing factors for agricultural production can be substantial. We investigate the role of an indigenous social network in Ethiopia, the iddir, in facilitating factor market transactions among smallholder farmers. Using detailed longitudinal household survey data and employing a difference-in-differences approach, we find that iddir membership improves households’ access to factor markets. Specifically, we find that by joining an iddir network, households’ access to land, labor, and credit improves between 7 and 11 percentage points. Furthermore, our findings indicate that iddir networks crowd-out borrowing from local moneylenders (locally referred as Arata Abedari), a relatively expensive credit source, virtually without affecting borrowing from formal credit sources. These results improve our understanding of the role informal market arrangements, such as social networks, can play in mitigating factor market inefficiencies in poor rural markets. The results also have important policy implications for designing alternative policy measures which aim to improve these markets.